The Lived Experience of Professional Mentorship and Its Implications for School-Based Mentoring Programs. Issue 2 (April 2020) - McNeven, Sean; McKay, Loraine; Main, Katherine
School-based mentoring (SBM) is an intervention that addresses the disengagement of "at-risk" youth. Currently, empirical evidence that SBM may help to stem youth disengagement remains largely inconclusive and inconsistent, and few studies have sought to examine the relational element of SBM. This article reports on a study that used a hermeneutic phenomenological methodology to identify and describe the constructs that constitute the lived experiences of two professional mentors working with young adolescents. The study's analysis revealed the mentor–mentee relationship as the principal operative element of such programs and identified mechanisms for the successful generation of mentor–mentee relational quality.